2012
DOI: 10.1126/scitranslmed.3004073
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax Vaccine–Induced Antibodies Provide Cross-Species Prediction of Survival to Aerosol Challenge

Abstract: Because clinical trials to assess the efficacy of vaccines against anthrax are not ethical or feasible, licensure for new anthrax vaccines will likely involve the Food and Drug Administration’s “Animal Rule,” a set of regulations that allow approval of products based on efficacy data only in animals combined with immunogenicity and safety data in animals and humans. US government sponsored animal studies have shown anthrax vaccine efficacy in a variety of settings. We examined data from 21 of those studies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 59 publications
3
58
0
Order By: Relevance
“…The primary immunogen in AVA is anthrax toxin protective antigen (PA). Serum anti-PA antibody levels are accurate immune correlates of protection in nonhuman primate (NHP) models of inhalation anthrax and for predicted probability of survival in humans (1)(2)(3). There is a significant lack of data in humans regarding the onset, duration, quantitative analysis, and functional activity of humoral antibody and cell-mediated immunity (CMI) responses following priming and boosting with AVA.…”
mentioning
confidence: 99%
“…The primary immunogen in AVA is anthrax toxin protective antigen (PA). Serum anti-PA antibody levels are accurate immune correlates of protection in nonhuman primate (NHP) models of inhalation anthrax and for predicted probability of survival in humans (1)(2)(3). There is a significant lack of data in humans regarding the onset, duration, quantitative analysis, and functional activity of humoral antibody and cell-mediated immunity (CMI) responses following priming and boosting with AVA.…”
mentioning
confidence: 99%
“…Previous studies have suggested that the PA-neutralizing humoral response is well-correlated with protective immunity (20). Here, a single inoculation of Ad5-PAopt resulted in robust and sustained anti-PA serum antibody and neutralizing antibody responses.…”
Section: Discussionmentioning
confidence: 67%
“…survival to an aerosol challenge. 8 Although, both AVA and rPA also induce TNA antibodies in vaccinated mice whether these TNA antibody levels in mice correlate with protection has not been firmly established. The data shown in Table 2 suggests the possible existence of such a correlate.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying premise being that the toxins released from vegetatively growing B. anthracis as a result of the germination of inhaled spores requires neutralization for the survival of vaccinated subjects. [6][7][8] Recently we reported that a cohort of rabbits immunized with a vaccinia-based PA vaccine created by the integration of the pag gene and an immune enhancing cytokine IL-15 into the genome of licensed smallpox vaccine (Wyeth/IL-15/PA), conferred sterile protection against an inhalation challenge exceeding 200 LD 50 of fully virulent Ames strain (A0462; pXO1 + pXO2 + ) spores. 9 The absence of bacteremia was also observed in the positive comparator group vaccinated with AVA suggesting perhaps PA based vaccines protect vaccinated subjects from inhalation anthrax by aborting the early events of the establishment of B. anthracis infection in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%